The last two moulting processes of Parafronurus youi and possible emergence evolution of Mayflies (Ephemeroptera: Heptageniidae). (2nd October 2018) - Luo, Juan-Yan; Hu, Ze; Ma, Zhen-Xing; Zhou, Chang-Fa
Abstract: Moulting processes of last instar nymph and subimago, longevity of subimago and imago of Parafronurus youi is observed and filmed in laboratory for the first time in China. The videos show clearly this species emerges in the afternoon (ca. 5:30 PM to 9:30 PM) on the object surface in water. The subimagos moult 14–19 h later before noon. Imago can survive for 3 to 4 days in lab. The data in the present paper and others as well as phylogeny do not provide clear evolutionary pattern of mayfly emergence location or time but a possibility maybe present: both the primitive mayfly nymph and adult can live and emerge on moist land, then adapt to aquatic habitats.